Perencanaan Desain Tempat Penampungan Sementara Sampah di Kecamatan Pabuaran Kabupaten Serang - Nurlaela Nurlaela; Frebhika Sri Puji Pangesti (Fakultas Teknik, 2023)
The pace of development, population, activities, and socioeconomic level of the community trigger an increase in the amount of waste generation that will be transported to landfills. The more human growth increases, the more waste generation will increase. Therefore, it is necessary to plan a Temporary Shelter (TPS) and waste transportation system in Pabuaran District, Serang Regency with the aim of reducing the negative impact of garbage accumulation and changing the behavior of people in Pabuaran District who still throw garbage in any place and to reduce the impact caused by the waste itself. The purpose of this study is to determine the rate and composition of waste and design a TPS that meets the criteria. Data that has been obtained from primary data sources and secondary data will be processed and analyzed. Data analysis is used as a determination and planning of waste TPS that will be applied in Pabuaran District. The results showed that the rate of waste generation every yearalways increases along with the increase in the number of residents. In 2021 the amount of waste generation in Pabuaran District was 26 m3 / day. Then in 2022 the amount of waste generation reached 27.24 m3 / day or 326.86 m3 / year and in 2031 it increased to 41.89 m3 / day or 502.73 m3 / year. year. So, the total land needs are based on the assessment of the units of space needed for the TPS building land in Pabuaran District covering an area of 99 m2.